1999
DOI: 10.1177/088626099014012004
|View full text |Cite
|
Sign up to set email alerts
|

Police-Reporting Behavior and Victim-Police Interactions as Described by Women in a Domestic Violence Shelter

Abstract: Previous research has addressed the motivations of domestic violence victims to contact police and police responses to domestic violence calls. In a study of 498 women who entered a battered women's shelter, a questionnaire was used to elicit types of abuse they experienced, police contact, and police-victim interactions. Approximately 58% of victims called the police in response to physical, emotional, and other forms of domestic abuse; however, less than one fourth of the batterers were arrested. Batterers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
56
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 10 publications
7
56
1
1
Order By: Relevance
“…The police typically are one of the first and most common responders to IPV victims (Coulter et al 1999), and many calls for assistance are received each day. Given the frequency of interaction between law enforcement officers and IPV victims, adequate training of officers (e.g., the dynamics of IPV, local resources such as battered women's shelters and counseling services) is crucial (Townsend et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The police typically are one of the first and most common responders to IPV victims (Coulter et al 1999), and many calls for assistance are received each day. Given the frequency of interaction between law enforcement officers and IPV victims, adequate training of officers (e.g., the dynamics of IPV, local resources such as battered women's shelters and counseling services) is crucial (Townsend et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…(Berk & Loseke, 1980-1981Berk & Newton, 1985;Buzawa & Hotaling, 2000;Stanko, 1985). From their interviews with 498 women in a domestic violence shelter in Florida, Coulter et al (1999) noted that 58% of the victims contacted the police to report some type of domestic abuse but less than one fourth of the offenders were arrested. Earlier Loseke (1980-1981) had found that the probability of an arrest declined significantly when the victim contacted the police, as opposed to a third party.…”
Section: Who Reported the Incident And The Decision To Arrestmentioning
confidence: 99%
“…Women who had been assaulted by the offender previously were less likely to report than those who had never been assaulted by that person before~Bach-man & Coker, 1995!. Some authors report that victims of a known offender or partner are less likely to report than victims of strangers~Block, 1974; Coulter et al, 1999;Fieldman-Summers, 1981;Gartner & MacMillan, 1995;Williams 1984!. Others have shown no effect~Bachman, 1998Bachman, & Coker, 1995;Hindelang, & Gottfredson, 1976;Felson et al, 1999;Skogan, 1976;Zawitz et al, 1993!.…”
mentioning
confidence: 92%
“…This is because young victims~especially male victims!, with their low reporting rate, are at greatest risk of assault~Skogan, 1976; Young et al, 1997!. There are consistent findings that the reporting rate increases with assault severitỹ Felson et al, 1999;Schneider, 1976;Skogan, 1976;Williams, 1984;Young et al, 1996!. Assaults with weapons~Bachman, 1998Block, 1974;Hindelang & Gottfredson, 1976;Williams, 1984!, assaults requiring medical attention~Bachman, 1998Bachman & Coker, 1995;Block, 1975;Williams, 1984!, physical abuse rather than emotional abusẽ Coulter et al, 1999;Felson et al, 1999, Hamilton & Coates, 1993; but see Gartner & MacMillan, 1995; who found no effect! and assaults compared to threats~Hindelang & Gottfredson, 1976!…”
mentioning
confidence: 94%
See 1 more Smart Citation